2002
DOI: 10.1080/00365520252903170
|View full text |Cite
|
Sign up to set email alerts
|

Can Sedation Reduce the Cardiac Stress During Gastrointestinal Endoscopy? A Study With Non-invasive Automated Cardiac Flow Measurement by Color Doppler Echocardiography

Abstract: Conscious sedation with midazolam does not reduce the cardiac stress during UGIE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…In addition, comparison of the groups with and without sedation revealed that the increments in serum cortisol, glucose and CRP levels were similar in both groups and that the values of the parameters obtained prior to and 10 min and 1 h after endoscopy were not statistically different between groups. These results agree with those reported by Yazawa et al (18), and suggest the view that sedation is not effective in reducing the endocrine response occurring during upper gastrointestinal endoscopy.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, comparison of the groups with and without sedation revealed that the increments in serum cortisol, glucose and CRP levels were similar in both groups and that the values of the parameters obtained prior to and 10 min and 1 h after endoscopy were not statistically different between groups. These results agree with those reported by Yazawa et al (18), and suggest the view that sedation is not effective in reducing the endocrine response occurring during upper gastrointestinal endoscopy.…”
Section: Discussionsupporting
confidence: 92%
“…Although many clinical trials have documented the feasibility of endoscopies without any sedation [3, 4, 5], and reduction of cardiac stress under sedation does not seem to be a strong argument [6, 7], given the choice, a majority of patients would undoubtedly prefer sedation [8]. Patients’ opinions probably depend not solely on their own personal experiences: the (poor) reputation of endoscopic procedures and patients’ fears have become a consideration in public health viz.…”
Section: Introductionmentioning
confidence: 99%
“…Benzodiazepine combinations: Because midazolam does not exhibit any analgesic effects, sole use for conscious sedation does not suppress sympathic stimulation due to esophageal intubation [29]. In order to reduce the harmful effects of sympathic stimulation benzodiazepines are usually combined with opioids.…”
Section: Benzodiazepinsmentioning
confidence: 99%